Urinary Angiotensinogen Level Predicts AKI in Acute Decompensated Heart Failure: A Prospective, Two-Stage Study - Yang, Xiaobing (J Am Soc Nephrol, 2015)
A major challenge in prevention and early treatment of acute cardiorenal syndrome (CRS) is the lack of high-performance predictors. To test the hypothesis that urinary angiotensinogen (uAGT) is an early predictor for acute CRS and 1-year prognosis in patients with acute decompensated heart failure (ADHF), we performed a prospective, two-stage, multicenter cohort study in patients with ADHF. In stage I (test set), 317 patients were recruited from four centers. In stage II (validation set), 119 patients were enrolled from two other centers. Daily uAGT levels were analyzed consecutively. AKI was defined according to Kidney Disease Improving Global Outcomes (KDIGO) Clinical Practice Guidelines. In stage I, 104 (32.8%) patients developed AKI during hospitalization. Daily uAGT peaked on the first hospital day in patients who subsequently developed AKI. After multivariable adjustment, the highest quartile of uAGT on admission was associated with a 50-fold increased risk of AKI compared with the lowest quartile. For predicting AKI, uAGT (area under the receiver-operating characteristic curve [AUC]=0.84) outperformed urinary neutrophil gelatinase-associated lipocalin (AUC=0.78), the urinary albumin/creatinine ratio (AUC=0.71), and the clinical model (AUC=0.77). Survivors in stage I were followed prospectively for 1 year after hospital discharge. The uAGT level independently predicted the risk of 1-year mortality (adjusted odds ratio, 4.5; 95% confidence interval, 2.1 to 9.5) and rehospitalization (adjusted odds ratio, 3.6; 95% confidence interval, 1.6 to 5.7). The ability of uAGT in predicting AKI was validated in stage II (AUC=0.79). In conclusion, uAGT is a strong predictor for acute CRS and 1-year prognosis in ADHF.